The Politics of Digital Agricultural Technologies: A Preliminary Review. Issue 2 (1st April 2019) - Rotz, Sarah; Duncan, Emily; Small, Matthew; Botschner, Janos; Dara, Rozita; Mosby, Ian; Reed, Mark; Fraser, Evan D.G.
Abstract: Digital technologies are being developed and adopted across the agro‐food system, from farm to fork. Within decision‐making spaces, however, little attention is being paid to political factors arising from such technological developments. This review draws from critical social sciences to examine emerging technologies and big data systems in agriculture and assesses some key issues arising in the field. We begin with an introduction and review of the so‐called 'digital revolution' and then briefly outline how political economy is effective for understanding major challenges for governing technologies and data systems in agriculture. These challenges include: (1) data ownership and control, (2) the production of technologies and data development, and (3) data security. We then use literature and examples to consider the extent to which the political and economic landscape can be shifted to support greater equity in agriculture, while reflecting on structural challenges and limits. In doing so, we emphasise that while there are significant systemic tensions between digital ag‐tech development and agroecological approaches, we do not see them as mutually exclusive per se. This article intends to provide decision‐makers, practitioners and scholars from a wide range of disciplines with a timely assessment of agro‐food digitalisation that attends to political economic factors. In doing so, this article contributes to policy and decision‐making discussions, which, from our perspective, continue to be rather technocentric in nature while paying little attention to how digital technologies can support agroecological systems specifically.